A STUDY OF ATMOSPHERIC PARAMETERS AND GAMMA RADIATION DURING TOTAL SOLAR ECLIPSE ON MARCH 9TH 2016 IN BALIKPAPAN, INDONESIA - PUTRI SUMARNA (NIM : 10212006), ANGGITA
Total solar eclipse is the astronomical phenomenon when the moon is between the sun and the earth, and moon’s umbra falling down to earth surface. This thesis aims to analyze the effects of the solar eclipse on the atmospheric parameters and cosmic ray radiation. On that period, the solar radiation that reaches the earth is totally blocked. Solar radiation is one of the cosmic radiation that is one of the natural radiation. Cosmic ray intensity and atmosphere parameter was measured during the solar eclipse on March 9th 2016 in Balikpapan, Indonesia. Count rate data and radiation count was taken using small volume scintillation detector NaI (Tl) crystal, radiation exposure data and radiation count was taken using survey meter GM tube, the atmosphere parameter data taken was pressure, temperature and humidity. Data acquisition last for two days before eclipse until two days after total solar eclipse. The hypothesizes for this experiment are the degradation of exposure rate, exposure, count and count rate when the solar eclipse occurred, where the degradation starts from the beginning of solar eclipse until the last eclipse, and there will be recovery on the next hour after the solar eclipse finished. Furthermore, there is a probability of temperature and pressure degradation, and humidity rising when solar eclipse. Data processing use statistical test ANOVA and Kruskal Wallis to determine the date that have significant differences. The result of this study which is a decrease of temperature with the rate of decline of 0.1ºC / min, increasing humidity at a rate of 1% / min and not observed gamma radiation when solar eclipse.